Penguatan Ikatan Pernikahan melalui Program “Pernikahan yang Dilahirkan Kembali” di GPPS Agape Bandung - Darmawan Darmawan; Fransisca Putri Cyndivania; Veronicha Nussa; Andronius Wedo; Hotmantri Simbolon (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
A faith-based marriage strengthening program is essential for building family resilience in urban congregations facing high divorce rates and declining marital quality. This community service activity aimed to revitalize the marital bonds of 22 couples in the Pria Sejati Bandung community and GPPS Agape Bandung congregation through the "Reborn Marriage" program. Using a participatory action research approach, a team of 12 facilitators implemented three main stages: initial coordination to identify needs and plan together with the community; an intensive one-day intervention consisting of teachings on grace, agape love, and divine purpose of marriage, along with testimony sharing, footwashing ritual, and gift giving; and a marriage commitment renewal ceremony. The results showed 100% attendance rate of all registered couples, active participation in every coaching session, and qualitative findings from focus group discussions including renewed spiritual intimacy, mutual forgiveness between spouses, and alignment of marital visions based on divine values. A total of 86% of couples expressed willingness to participate in regular follow-up mentoring, and local leaders emerged among participants who are ready to facilitate small groups after the program. Discussions confirmed that combining biblical teachings on agape love with experiential symbolic rituals can holistically transform marital relationships. This community-based intervention proves replicable in other local communities and churches in urban settings, especially those seeking to strengthen family resilience through integrated pastoral care and participatory action.